Prank dalam Perspektif Al-Qur’an dan Hadis - Purwaningsih, Rahma Fitria; Witro, Doli (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2021)
The 21st century is the century of technological development in the information and communication sector. In March 2019, it was shown that out of 150 million active Indonesian users, 88% were confirmed to have accessed YouTube. Being the best-selling application motivates content creators to create exciting content that can continue to attract fans. Lately, netizens are very fond of entertainment-based content which is closely related to pranks. One of the best-selling prank videos that topped trending number 1 in January 2019 was a YouTuber video disguised as a vagrant and a crazy person with his wife. This article aims to provide an insight into how pranks (joking) are taught in Islam based on the perspective of the Al-Quran and Hadith so that the content or videos created do not harm YouTubers. This research is qualitative research with the character of library research. The research data is obtained from books, international and national journals, research reports, articles from news media, magazines related to prank. After the data is collected, read and understand related to the problem being researched. Then the data were analyzed using data analysis techniques Miles and Huberman, namely data reduction, data presentation, and concluding. The results showed that even though entertainment by joking and laughing is a form of interactive communication that indicates happiness is also human nature. However, the culture of joking that is trending like pranks is not justified. On the other hand, prank becomes an act of humour that does not meet the ethical requirements of joking on the Islamic viewpoint.